História da Matemática na Formação Inicial de Professores de Matemática: um olhar para as questões do Provão e Enade no período de 1998 a 2021 - Dalbon, Eliane Siviero da Silva (2022)
The general objective of this research was to characterize the ways in which History of Mathematics has been addressed in the national exams that assess the Mathematics course, being the Exame Nacional de Cursos (ENC), better known as Provão, and the Exame Nacional de Desempenho dos estudantes (Enade). For this, all editions of these exams in which the Mathematics course was evaluated until the period of 2021 were considered, comprising the following years: Provão – 1998; 1999; 2000; 2001; 2002 and 2003, and Enade – 2005; 2008; 2011; 2014; 2017 and 2021. The methodological framework used in the work was the analysis of qualitative structuring content, from which we established three categories of analyses according to what was expected to be mobilized by the students about historical knowledge in the resolution of the questions, and a fourth category, that emerged from the analyses. In all, 29 (twenty-nine) questions were selected: 13 (thirteen) in the category "Constitution of the problem"; 5 (five) in the category "Motivational use"; 6 (six) in the category "Didactic Resource"; and 5 (five) in the category "Historical potential". In general, the History of Mathematics in Provão and Enade has mainly evaluated the capacity of students of applying formulas and methods, being listed only as specific content for the Degree; however, until the 2011 edition of Enade, and in the editions of Provão in which we have found the guidelines, the profile taken as a reference for both the Bachelor's degree and the Teachers’ training course degree was of a professional capable of conceiving mathematics as a rigorous, formal and deductive body of knowledge, product of human activity, and historically constructed. Since the 2014 edition of Enade, this profile is no longer listed for both modalities, restricted only to the Degree. Finally, we could notice, in the last editions of Enade, an approach directed to meeting what is expected that a student in the initial training knows of the History of Mathematics, and how to incorporate it in the classroom.